REALITA KINERJA PEGAWAI - Hunein, Hamida (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
Providing satisfying service is a business goal, Why? because it's a source of company revenue. Therefore, improving the quality of employees is the right way. Encourage HR to present friendly, fast, responsive behaviors and provide good results as leaders. This study aims to explore information related to employee performance in private tertiary institutions. Through a qualitative approach, it is hoped that data can be useful for interested parties, both in improving the implementation of management and the development of HR itself. The results of the study suggest that the lack of performance is in the management system and the role of the leader. Often SOPs are made if a job or task faces a problem, while leaders with limited knowledge of management tend to be passive, not even able to present policy products. This condition makes employee performance growth slow. Keywords : Quality, Quantity, Time, Cost